The Effect of Social Media Marketing on Competitive Advantage and Company Performance - Khoiriyah Trianti; Karina Utami Anastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study focused on Amangtiwi Micro Small and Medium Enterprises (MSME) in Malang Regency, to examine the effect of social media marketing on competitive advantage and company performance. This study processed primary data obtained using a questionnaire distributed to 148 MSME. The sample was selected using stratified random sampling method. This study uses a cluster sampling method involving 148 respondents and uses PLS (Partial Least Square) analysis tools with SmartPLS 3.0 software. The results revealed that using social media for marketing has an effect on the competitive advantage and performance of MSME.